Molecular Docking Studies of Phytochemicals from Five Medicinal Plants against Resistance genes Protein isolated from MDR Salmonella Typhimurium - Gaikwad, Rahul Prabhu (Asian Journal of Pharmaceutics (AJP), 2023)
Introduction: In the present study, the antibacterial activity against multidrug-resistant (MDR) Salmonella Typhimurium of different extracts of Five Medicinal Plants was investigated along with their phytochemical analysis by gas chromatography-mass spectrometry (GC-MS) and Molecular Docking Studies of Phytochemicals to explore antimicrobial compounds present in extracts. Materials and Methods: The antibacterial activities of different extracts of Five Medicinal Plants were evaluated against isolated MDR S. Typhimurium by disc diffusion method. Docking studies were carried out using different required docking platforms along with phytochemical analysis by GC-MS. Results and Discussion: The phytochemical analysis by quantitative and qualitative methods of the extract of Allium sativum, Bridelia micrantha, Citrus lemon, Glycyrrhiza glabra, and Punica granatum showed presence of amino acids, alkaloids, glycosides, saponins, flavonoids, steroids, and terpenoids. It was discovered that crude extracts of these plants worked well against MDR S. Typhimurium. The zone of inhibition values for the crude extract of A. sativum, B. micrantha, C. lemon, G. glabra, and P. granatum was found to be, 10.12 ± 1.71 mm, 23.50 ± 0.00 mm, 26.60 ± 0.64 mm, 29.20 ± 0.11 mm, and 19.50 ± 0.00 mm, respectively. Docking results of phyto-ligand with selected resistance genes proteins reveals that the binding energy ranges from −2.9 to −9.2 kcal/moL. G. glabra roots (Ligand 6-Androstanone, 3-(3, 4-dimethylphenyl)-3-methyl) showed the lowest binding energy of −9.2 kcal/moL. Conclusion: To produce broad-spectrum antimicrobial compounds, it is still important to assess the antibacterial potential of medicinal plants. Traditional medicine is one of the most generally available types of treatment in disadvantaged countries. According to the study’s findings, phytochemicals from five medicinal plants extract have in vitro antibacterial activity along with phyto-ligand docking analysis providing early evidence that the plants may be used to treat MDR infections.